INTEGRATING INSTAGRAM TO SCAFFOLD STUDENTS’ WRITING IN EFL CLASSROOM - Rizkullah, Naufal (ENGLISH JOURNAL, 2020)
Technology is one of important aspects that has very crucial effects on learning process nowadays. This study investigates the integration of technology in EFL Classroom especially in Writing class. The study employs classroom action research in which observation and documentation were used as data collection. The study was done in a vocational school in Indonesia. The results show that students have problems in their writing and Instagram can be used as a tool to scaffold their writing in terms of motivation and positive learning environment.